МЕСТО ЛЕКСЕМ «МАТЬ»/ «АНА», «ОТЕЦ/АТА» В ВЫРАЖЕНИИ КОНЦЕПТА «РОДИНА»/ «ЎАТАН» В РУССКОМ И КАРАКАЛПАКСКОМ ЯЗЫКАХ - Турабаева, Н.А. (SCIENCE and SOCIETY, 2024)
The concept of "Motherland" is universal and is reflected in many languages of the world. This article examines the place of the lexemes "mother" / "ana", "father / ata" in the expression of the concept "Motherland" / "Oatan" in the Russian and Karakalpak languages. The place of the family in the hierarchy of filling the meaning of the concept Motherland in the Russian language is determined through the analysis of the lexemes mother-father.